Terpene Synthase-b and Terpene Synthase-e/f Genes Produce Monoterpenes for Phalaenopsis bellina Floral Scent - Huang, Hsin; Kuo, Yi-Wei; Chuang, Yu-Chen; Yang, Ya-Ping; Huang, Li-Min; Jeng, Mei-Fen; Chen, Wen-Huei; Chen, Hong-Hwa (Frontiers in Plant Science, 2021)
Orchids are the most species-rich plants and highly interact with pollinators via visual or olfactory cues. Biosynthesis and emission of volatile organic compounds (VOCs) to the atmosphere facilitate the olfactory cues and ensure successful pollination. Phalaenopsis bellina is a scented orchid with monoterpenes as major VOCs, comprising linalool, geraniol and their derivatives. Comparative transcriptomics analysis identified 4 terpene synthase-b (TPS-b) genes and 2 TPS-e/f genes with differential gene expression between scented and scentless Phalaenopsis species. Here, we confirmed their differential expression between scented and scentless Phalaenopsis orchids and excluded one TPS-b candidate. We analyzed the temporal and spatial expression and functionally characterized these TPSs. Both TPS-b and TPS-e/f genes showed increased expression on blooming day or 3 days post-anthesis (D+3) before the optimal emission of floral scent on D+5, with especially high expression of PbTPS5 and PbTPS10. The TPS-b genes expressed exclusively in reproductive organs, whereas the TPS-e/f genes expressed in both reproductive and vegetative organs. in planta functional characterization of both PbTPS5 and PbTPS10 in tobacco and scentless Phalaenopsis plants did not produce terpenoids. Further ectopic expression in scented Phalaenopsis cultivar P. I-Hsin Venus showed that linalool was the main product, with PbTPS10 displaying 3-fold higher activity than PbTPS5. On in vitro enzyme assay with purified recombinant TPS-b proteins ectopically expressed in E. coli, geraniol was the product catalyzed by PbTPS5 and PbTPS9. PbTPS3 was a linalool/(b)-cis-ocimene synthase and PbTPS4 a linalool synthase. In conclusion, both TPS-b and TPS-e/f enzymes orchestrated floral monoterpene biosynthesis in P. bellina.